Investigación de mercado para evaluar el impacto socio-económico originado por el incremento de las operaciones del aeropuerto internacional Cotopaxi, en el sector hotelero de la ciudad de Latacunga - Vilca Llano, Darwin Patricio (2015)
For development this work was collected information primary and secondary level, the information gathered was obtained through interviews, surveys, observations, and others. Thus, it was found that the main problem is the low level of socio-economic impact study on the hospitality industry by operation of the Cotopaxi International Airport. This research presents themes such as tourism, levels of export and import from the Airport, main techniques to assess the economic and social impact, of the hospitality allowing to assess scenario and propose solutions for improvement in these sectors.